Analysis of Service Quality on Customer Satisfaction at Merchant Mixue Summarecon Digital Center Branch, Tangerang - Tannady, Hendy; Aryanti, Mitha Novi; Julieta, Levana; Salsabila, Hanifah Dzaky; Octavia, Ditha (HM Publisher, 2023)
Product quality is determined by several factors, one of which is customer satisfaction. Unfortunately, many companies are more concerned with the products or services offered and are not concerned with service quality. This study aimed at assessing the service quality provided by Mixue at the Summarecon Digital Center branch. This research was a descriptive study. The research sample was Mixue visitors at the Summarecon Gading Serpong branch, Tangerang. The inclusion criteria for research subjects were 17-30 years old and willing to fill out a research form via Google form. A total of 30 respondents took part in this study. There are 10 indicators of questions which include ease of parking, the comfort of the place, cleanliness of the outlet, speed of cashiers in payment, additional facilities, speed of employees in serving, employee friendliness, employee knowledge of products, affordable prices, and product suitability with photos on the menu. After obtaining data from respondents, the importance and performance of the Mixture were analyzed with gap analysis, then the indicators were calculated. The results of the study show that the main focus components for increasing customer satisfaction are the comfort of the place, ease of parking, and the speed of the cashier in payment, which is in quadrants 1 and 2. Employee friendliness and cleanliness of toilets are also important and affect Mixue customer satisfaction which is in quadrant 4. In conclusion, Mixue at the Summarecon Digital Center branch needs to pay attention to several things to increase customer satisfaction with its services. Things that need to be prioritized are the convenience of the store, the speed of cashier service, the price according to the quality of the goods, the conformity of the products being sold with menu photos, and employee knowledge regarding the product.